2018
DOI: 10.1007/s40618-018-0908-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of cervical lymph node metastasis risk factors in patients with papillary thyroid microcarcinoma

Abstract: Purpose Lymph node metastasis (LNM) is a vital prognosis factor in patients with papillary thyroid microcarcinoma (PTMC). The study tried to identify clinicopathological factors for LNM of PTMC. Methods The clinicopathological data of 1031 patients with PTMC were extracted and analyzed. Univariate and multivariate analyses were used to identify risk factors associated with cervical lymph node metastasis. ROC analysis was used to determine the ideal critical points of the sum of the maximum diameter of multifoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
37
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 31 publications
11
37
2
3
Order By: Relevance
“…Our results are similar to a study by Kwak et al who showed a rate of lateral metastasis of 3.7% in their cohort [21]. However, Luo et al showed a rate of 5.6% of lateral LN metastasis, and this was associated with multifocality and ETE [22]. Our results confirmed that U/S mapping is a highly reliable and accurate tool in identifying metastatic LN and guiding the surgeon for precise neck dissection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are similar to a study by Kwak et al who showed a rate of lateral metastasis of 3.7% in their cohort [21]. However, Luo et al showed a rate of 5.6% of lateral LN metastasis, and this was associated with multifocality and ETE [22]. Our results confirmed that U/S mapping is a highly reliable and accurate tool in identifying metastatic LN and guiding the surgeon for precise neck dissection.…”
Section: Discussionsupporting
confidence: 91%
“…Central LN metastasis can occur in up to 29.3% and lateral lymph node metastasis in 3.7-5.6% of PTMC patients [20][21][22], and this is associated with locoregional re-occurrence and adverse outcomes [23,24]. ETE is another risk factor that can affect the decision for total vs. hemithyroidectomy [16,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical stage of ETE belongs to T3, so we excluded ETE in this study. Tumor location at the superior pole and ipsilateral central lymph node positivity are also independent high-risk factors for lateral neck metastasis in PTMC patients, consistent with other studies [20,21] . However, our study did not find that sex, multifocality or age were high-risk factors for LNLN metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…There is a well-documented, worldwide trend showing an rapid increasing incidence of PTC in recent decades (2)(3)(4). This increase has been predominantly an increase in PTMC, accounting for 50% of PTCs (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%